Advances in quantum systems in chemistry, physics, and biology : Selected proceedings of QSCP-XXIII (Kruger Park, South Africa, September 2018) /: Selected proceedings of QSCP-XXIII (Kruger Park, South Africa, September 2018). (2020) - Unknown
No abstract available